2015
DOI: 10.1186/s12936-015-0873-2
|View full text |Cite
|
Sign up to set email alerts
|

Malaria impact of large dams in sub-Saharan Africa: maps, estimates and predictions

Abstract: BackgroundWhile there is growing recognition of the malaria impacts of large dams in sub-Saharan Africa, the cumulative malaria impact of reservoirs associated with current and future dam developments has not been quantified. The objective of this study was to estimate the current and predict the future impact of large dams on malaria in different eco-epidemiological settings across sub-Saharan Africa.MethodsThe locations of 1268 existing and 78 planned large dams in sub-Saharan Africa were mapped against the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 32 publications
(30 reference statements)
1
53
2
1
Order By: Relevance
“…However, in areas of unstable transmission, the annual malaria incidence is likely to increase twofold to threefold in the 2080s when compared to 2010 and this difference was statistically significant (χ 2  = 13.061; df = 2; P  < 0.001) in both RCPs.
Fig. 2Estimated average annual malaria incidence in the 2020s, 2050s and 2080s in communities living close to (<5 km) and further away (5–10 km) from dam-associated reservoirs in sub-Saharan Africa, using two future climate scenarios (RCP 2.6 and RCP 8.5).Data for 2010 is included for comparison: source Kibret et al [11]
…”
Section: Resultsmentioning
confidence: 99%
“…However, in areas of unstable transmission, the annual malaria incidence is likely to increase twofold to threefold in the 2080s when compared to 2010 and this difference was statistically significant (χ 2  = 13.061; df = 2; P  < 0.001) in both RCPs.
Fig. 2Estimated average annual malaria incidence in the 2020s, 2050s and 2080s in communities living close to (<5 km) and further away (5–10 km) from dam-associated reservoirs in sub-Saharan Africa, using two future climate scenarios (RCP 2.6 and RCP 8.5).Data for 2010 is included for comparison: source Kibret et al [11]
…”
Section: Resultsmentioning
confidence: 99%
“…Environmental modification such as dam construction has long been recognized to enhance LF transmission by creating ideal breeding sites for mosquito vectors, thereby bringing both the vectors and disease closer to the people [4]. As Nigeria continues its implementation on the LF Elimination Programme, a basic problem envisaged is the dearth of information on the distribution of LF in most endemic states of the country [5].…”
Section: Introductionmentioning
confidence: 99%
“…Dams may also adversely affect public health. For example, WLE research has shown that by providing breeding habitat for anopheles mosquitoes, 1,268 large dams in subSaharan Africa elevate the risk of malaria for 15 million people and cause at least 1.1 million people to contract the disease each year (Kibret et al 2015). If mitigation measures are not improved, these numbers could triple by the end of the century as a result of population growth in combination with climate change-without even considering effects of new dam construction (Kibret et al 2016).…”
Section: Recommendationsmentioning
confidence: 99%